Reading comprehension studies in the last decade: global trends and future direction of Indonesia language researches - Suyanto, Edi; Samhati, Siti; Aisyah, Nenden Lilis; Antrakusuma, Bayu (International Journal of Evaluation and Research in Education (IJERE), 2024)
The publication trend related to reading comprehension studies in the last decade has sharply grown. Nevertheless, studies offering comprehensive bibliometric and bibliographic reviews related to reading comprehension studies have not been conducted nor also found in the journal or conference proceeding. The purpose of this study is to present a bibliographic and bibliometric review of the numerous documents studying reading comprehension skills. A bibliometric analysis was performed to carry out this study whereby 1,681 eligible documents from the Scopus database published from 2013 to 2022 were used as research materials. Results showed that in 2013-2022, the publication trend of reading comprehension studies slightly increased while the citation trend on the documents regarding reading comprehension skills tended to fall sharply. Additionally, at least there were several major emerging themes of reading comprehension studies such as methodology, language, educational level, reading disability, reading intervention, reading comprehension predictor, and moderating factor of reading comprehension. This study implies that researchers in the field of Indonesian language education can focus on the utilization of Indonesian textbooks in investigating learners’ reading comprehension skills, develop innovative and effective reading interventions to enhance learners’ reading comprehension skills, and explore some other moderating factors of reading comprehension skills such as ethnicity, culture, geographical location, and textbook topic.